THE RICHARD'S MASCULINITY IN FILM LOVE FOR SALE 1 - Ramadhana, Reza Chandra; Utami, Citra Dewi (Capture : Jurnal Seni Media Rekam, 2020)
This research focuses on the masculinity of a male character named Richard Achmad in the film Love for Sale 1 directed by Andibachtiar Yusuf. The purpose of this study was to determine the social construction of men depicted in the masculinity of Richard's character. This type of research is qualitative research with the technique of collecting Saturated Sampling data. Observation and Literature Study method as a data collection method. Data analysis uses Interactive Data Analysis including data reduction, data display and conclusion drawing / verification. The reading of John Beynon's masculinity is used as an approach to find the masculinity in Richard's character. The results showed that the male social construction built in the film Love for Sale 1 is a representative of the social construction picture that exists in real life. There are similarities in the social construction of masculinity between Richard's character in the film Love for Sale 1 and in real life.